Ability of murid rodents to find buried seeds in the Monte desert - Taraborelli, Paula Andrea (2009)
Rodents have developed a great capacity to for finding and storing seeds, and the ability of each species to find seeds in sufficient numbers could determine rodent abundance. To investigate this ability, we compared the differential ability of four murid rodents (Akodon molinae, Graomys griseoflavus, Calomys musculinus and Eligmodontia typus) to detect buried seeds. We also measured the variables (seed type, number of seeds in caches, soil depth and soil moisture) that would be affecting such ability. Results showed a differential ability to find seeds among rodents, E. typus was the most successful species, and C. musculinus and G. griseoflavus were the least successful. Conditions of wet sand and grouped seeds were the most favourable for murids to find higher number of seeds. These rodents showed preference for the sunflower seed, which is large, with good hygroscopic capacity and high in lipids, whereas millet is the opposite. The use of food storage strategies would give murid species a differential adaptive advantage, providing them with a greater ability to locate and exploit food sources more efficiently in periods of lower food abundance and after rainfall events.